Perhitungan Variance Biaya Produksi Proyek No PTC-0213-2212 Pada PT Proserv Batam - Seto Sulaksono Adi Wibowo; Maharani Anggi Lestari (Politeknik Negeri Batam, 2014)
This study discusses the production cost variance. The purpose of this study was to calculate the total difference in the budgeted costs and the actual cost to complete the project job number PTC-0213-2212. This research was conducted by comparing the cost of the budget (budget) as determined by actual production costs are real. The object of this research project is job number PTC-0213-2212 which manufactures wellhead control panel with client Thai Nippon Steel & Sumkin Engineering & Construction Corp., Ltd. This research was conducted at PT Proserv Batam which is a manufacturing company engaged in oil and gas. Cost of production is an important element for companies, especially companies engaged in manufacturing. For manufacturing companies, the cost of production is the main focus of management in particular for the production can be controlled. One analytical tool that can control the production cost variance analysis. The total variance of the results of this study is 27,241.21 (favorable). The variance in total variance obtained from raw material costs of 7,164.19, variance direct labor costs of 13,105.54, variance variable overhead costs amounted to 2,335.00, and the variance fixed overhead costs amounted to 4,186.48.